Larvicidal Potential of Leaf Extracts and Purified Fraction of Datura Stramonium against Culex Quinquefasciatu Smosquitoes - D.G.W, Chintem; H.C, Nzelibe; D.B, James; S.U, Albaba; H.T, Grillo (International Journal of Natural Sciences Research, 2014)
The larvicidal potential of Datura stramonium leaf extracts against Culex quinquefasciatusmosquitoe species was evaluated. Mosquitoes larvicidal activities of crude aqueous, ethanol, ethylacetate, n-hexane and purified leaf extracts of D. stramonium were tested against the early fourth-instar larvae of C. quinquefasciatusmosquitoes species. Larvicidal toxicity assay were carried out against the late third and early fourth instar larvae of C. quinquefasciatus (Dipteral: Culicidae) and larval mortality was observed after 12 h, 24 h and 48h of treatments. Column chromatography was used to isolate the fraction with the highest Larvicidal activity. FTIR and GC-MS were used for structural identification. Phytochemical studies revealed the presence of alkaloid, tannins and terpenoids in D. stramonium Ethanol extract. The effective larvicidal activity was observed in ethanol extract of D. stramonium against C. quinquefasciatusmosquitoes larvae with percentage mortality of 96% at 1000ppm after 24hr. The lethal concentration were found LC50 (2.565ppm) and LC90 (17.724 ppm) of ethanol extract respectively. Fraction one (1) of D. stramonium Ethanol Extract (DSEE-F1) had the highest percentage mortality of 99 % after 24 hours with LC50 and LC90 of 4.390 ppm and 6.957ppm respectively. A single spot was obtained by preparative-TLC with Rf value of 0.73 while the GC-MS analysis revealed presence of Heneicosane in DSEE-F1. Lethal concentration LC50 of Heneicosane was found to be (2.21 ppm) compared to the standard dichlorvos LC50 (2.04 ppm). The present work recommends that Heneicosane compounds could serve as potent larvicidal agent for mosquitoe control.